Production of hard tofu from calcium fortified soybean milk and its chemical and sensory properties - Eadmusik, Sunee; Puwastien, Prapasri; Nitithamyong, Anadi (Asia-Pacific Journal of Science and Technology, 2017)
Hard tofu, a product from soybean milk, is one of the common food products in Asia. Soybean milk with soybean to water ratio varying from 1:6 to 1:8 was prepared in triplicate. The weight of soybean used in all experiments was 200 g. Calcium salt used to fortify soybean milk was 120 mg Ca/100 ml together with sequestering and stabilizing agents. Calcium-fortified hard tofu was produced by coagulation of the calcium-fortified soybean milk with saturated MgSO4. Nutritive values and bioaccessibility of calcium in calcium-fortified tofu were determined. The yields of total solid and protein in calcium-fortified tofu prepared from soybean milk with a soybean to water ratio of 1:6 were the lowest (78.9+5.4 and 33.0+1.6 g, respectively). In contrast, the highest yields of both parameters (total solid, 90.5 +3.8 g and protein, 45.4+4.2 g) were obtained in tofu prepared from soybean milk with the ratio of 1:8. The tofu also contained the highest amount of total calcium (1947+54 mg). As a result, the soybean to water ratio of 1:8 was selected to be used for calcium-fortified tofu production with and without adding of sequestering and stabilizing agents. The yield of total solid in the calcium-fortified tofu of both types was in the same range. However, the total protein yield of tofu with additives was significantly higher than that without the additives, 45.4+4.2 g compared to 37.0+1.8 g, respectively. Carrageenan, used as stabilizing agent in preparation of the fortified tofu, may play an important role in holding water and protein, resulted in higher tofu yield with higher protein content. The addition of the sequestering and stabilizing agents did not show any significant effects on the total amount of calcium in the calcium-fortified tofu. The calcium fortified tofu was well accepted, however, its calcium bioaccessibility was lower than that of milk powder which is likely due to the presence of phytate.